Associations of Childhood Maltreatment With Suicidal Behavior Among Chinese Adolescents: Does It Differ Based on Gender and Biological Rhythm? - Xie, Yang; Xu, Huiqiong; Wang, Baolin; Wu, Xiaoyan; Tao, Shuman; Wan, Yuhui; Tao, Fangbiao (Frontiers in Psychiatry, 2022)
Background: The impact of biological rhythm disorder (BRD) on the association of childhood maltreatment (CM) and suicidal behaviour in adolescents remains unclear. CM increases the risk of suicidal ideation (SI), suicidal planning (SP), and suicidal attempts (SAs). There is less investigation on gender differences in CM’s effects on suicidal behaviour. It is unknown whether the impacts vary with different levels of BRD. Aims: To identify gender differences in CM’s effects on suicidal behaviour and to investigate these impacts at different levels of BRD. Method: The analysis is based on data from 7,986 adolescents recruited from three cities in China between October and December 2019. All participants, aged 14.7±2 years, filled out standard questionnaires involving CM, BRD, and suicidal behaviour. Results: A total of 22.9%, 10.8%, and 4.7% of the adolescents reported SI/SP/SAs in the past year. Girls are more likely to engage in SI and SP when exposed to the highest level of CM; boys are more likely to engage in SAs than girls. A significant relationship between moderate levels of CM and SI/SP/SAs was only observed in girls exposed to low BRD. Moderate CM is only significantly associated with SI in boys exposed to low BRD. The percentage of low BRD adolescents who experienced high CM was 31.4%, whereas 58% of high BRD adolescents experienced high CM in SI. Adolescents with high BRD were more likely to experience high levels of CM in SP and SAs. Conclusions: Adolescents at high risk of suicidal behaviour in relation to CM should be targeted accordingly. Improving biological rhythm in adolescents who experience CM could help prevent them from engaging in suicidal behaviour.